2016
DOI: 10.1111/1468-4446.12205
|View full text |Cite
|
Sign up to set email alerts
|

The remaining core: a fresh look at religiosity trends in Great Britain

Abstract: In recent years, there has been a growing argument that the end product of secularization may not be a disappearance of all things religious, but rather a polarization between a larger secular group in society and smaller religiously fervent and active communities. Yet, there has been little empirical testing of this theory in contexts of advanced secularization. The aim of this paper is to fill this gap by studying individual belief and religiosity trends over the past four decades in Great Britain, searching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…As such, the observed growth in the number of seculars is entirely fuelled by the fall in religiosity of individuals at the religious middle ground, for instance, the nominal and ambivalent affiliates (Olson and Beckworth, 2011; Voas, 2009). Patterns congruent with the polarization hypothesis have been reported for many Western countries, most of them with a long history of secularization (Achterberg et al, 2009; Bibby, 2011; Dilmaghani, 2018; Kaufmann et al, 2012; Reimer, 2017; Ribberink et al, 2013; Wilkins-Laflamme, 2014, 2016a). The present article contributes to this literature by proposing a methodology to quantify the degree of religious polarization.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…As such, the observed growth in the number of seculars is entirely fuelled by the fall in religiosity of individuals at the religious middle ground, for instance, the nominal and ambivalent affiliates (Olson and Beckworth, 2011; Voas, 2009). Patterns congruent with the polarization hypothesis have been reported for many Western countries, most of them with a long history of secularization (Achterberg et al, 2009; Bibby, 2011; Dilmaghani, 2018; Kaufmann et al, 2012; Reimer, 2017; Ribberink et al, 2013; Wilkins-Laflamme, 2014, 2016a). The present article contributes to this literature by proposing a methodology to quantify the degree of religious polarization.…”
Section: Introductionsupporting
confidence: 61%
“…Focusing on the European context, Kaufmann et al (2012) defined polarization as the stagnation or reversal of the trend of religious decline and reported compatible evidence for a few countries. Wilkins-Laflamme (2016a), analysing British data from 1991, 1998 and 2008, found mounting differences in the degree of religious commitment and attitude towards public religion, between the growing segment of the unaffiliated and the more stable portion of the highly religious. For Canada, the stabilization of the number of regular churchgoers has been reported by various scholars (Bibby, 2004; Bowen, 2004), in the face of sharp drops in average religious attendance rates (Eagle, 2011a; Hay, 2014).…”
Section: Highlights Of the Past Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The UK is a theoretically interesting case to explore variation in parental values between religious groups and between religious and non‐religious parents due to its high degree of religious diversity and increasing levels of secularization (Wilkins‐LaFlamme ). Scourfield et al () found that the intergenerational transmission of religion, and religious values and practices, was particularly strong in Muslim families.…”
Section: Beyond Class: Religion Religiosity and Racialized Groupsmentioning
confidence: 99%
“…Research on ‘religious polarization’ may be useful for explaining important cleavages in parental values. According to the religious polarization thesis, growing secularization in many societies, including the UK, does not simply translate into the disappearance of religion but an increasingly sharp divide between a ‘large secular group of individuals on the one hand and smaller actively religious communities on the other’ – who each hold distinctive beliefs, attitudes and values (Wilkins‐LaFlamme : 650). This may mean that the largest differences in parenting values are simply between religious and secular parents.…”
Section: Beyond Class: Religion Religiosity and Racialized Groupsmentioning
confidence: 99%